Differences in DNA fragmentation following transient cerebral or decapitation ischemia in rats. - MacManus, J; Hill, I; Preston, E; Rasquinha, I; Walker, T; Buchan, A (1995)
The time course of appearance of cells with DNA damage was studied in rats following transient severe forebrain ischemia. This DNA damage could be detected by in situ end-labeling on brain sections. The breaks in DNA appeared selectively by day 1 in the striatum and later in the CA1 region of the hippocampus. It was possible by double labeling to show that there was no DNA damage in astrocytes. The DNA breaks consisted of laddered DNA fragments indicative of an ordered apoptotic type of internucleosomal cleavage, which persisted without smearing for up to 7 days of reperfusion. In contrast, the DNA breaks following ischemia induced by decapitation were random and, after gel electrophoresis, consisted of smeared fragments of multiple sizes. There was some early regional cellular death, restricted to the dentate of the hippocampus, prior to the pannecrotic degeneration. It is concluded that transient forebrain ischemia leads to a type of neuronal destruction that is not random necrosis but that shares some component of the apoptotic cell death pathway.